EAR DAGGER FROM THE 14TH TO THE 19TH CENTURIES: AN ARTISTIC FUNCTIONAL STUDY OF SAMPIES - Hamada THABET; Rabea Sayed (Shedet, 2023)
This paper focuses on the Ear Dagger in Andalusia, Europe and India by studying samples of the Ear Dagger. This study discusses the Ear Dagger’s origins and reasons for its prevalence in Granada. It also explores the name which was after the general design of the handle resembling earrings, especially in the 14th century. The dagger took other names among the European soldiers' sects. It had various artistic styles. This paper discusses the styles of the Ear Dagger. It had various artistic designs, such as the Nasrid style of the Nasrid dynasty in Andalusia. It spread with simple design differences across Europe as an influence of Andalusian Islamic arts. It was introduced with a specific pattern in India during the reign of the Mughal emperors. Furthermore, it had several functions not limited to war. It appeared in the paintings of the nobles in Europe and the manuscript paintings of India as a part of the costume of rulers and emirs. The Arab culture in Andalusia, Europe and Mughal were the primary influences on the design and use the Ear Dagger. The paper also highlights the relationship between the decoration and function of the Ear Dagger and examines the dagger’s manufacturing materials and methods.The study concludes that the Nasrid style is the oldest. It mostly appeared in the 14th century, then it spread across Europe as an effect of the Andalusian Islamic arts. This study proves that the dimensions of the Ear Dagger suited the function. This design on the end of the dagger helped maintain the stability of the dagger while it was worn in the belt by the soldiers during battles, so it had a functional purpose.